2002
DOI: 10.1128/mcb.22.2.587-598.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of Fra-1 and Consequent Activation of AP-1 Occur Extracellular Signal-Regulated Kinase Dependently

Abstract: Mitogen-activated protein (MAP) kinase, extracellular-signal-regulated kinases (ERKs) play an important role in activating AP-1-dependent transcription. Studies using the JB6 mouse epidermal model and a transgenic mouse model have established a requirement for AP-1-dependent transcription in tumor promotion. Tumor promoters such as 12-O-tetradecanoylphorbol-13-acetate (TPA) and epidermal growth factor induce activator protein 1 (AP-1) activity and neoplastic transformation in JB6 transformation-sensitive (P ؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 65 publications
10
91
1
Order By: Relevance
“…Treatment of the cells with the mitogen TPA to induce phosphorylation and activation of Fra-1 (Young et al, 2002) did not alter the abundance of Fra-1/TBP-1 complexes. However, TBP-1 immunoprecipitates contained Fra-1 species of differing mobilities on SDS-polyacrylamide gel electrophoresis gels, a likely indication that multiple phosphorylation states of the protein were present .…”
Section: Resultsmentioning
confidence: 81%
“…Treatment of the cells with the mitogen TPA to induce phosphorylation and activation of Fra-1 (Young et al, 2002) did not alter the abundance of Fra-1/TBP-1 complexes. However, TBP-1 immunoprecipitates contained Fra-1 species of differing mobilities on SDS-polyacrylamide gel electrophoresis gels, a likely indication that multiple phosphorylation states of the protein were present .…”
Section: Resultsmentioning
confidence: 81%
“…In line with this notion, recent studies have shown that the AP-1 family member Fra-1 (Fosl1) is essential for efficient neoplastic transformation of keratinocytes (Young et al, 2002), whereas expression of the membrane-bound metalloproteinase Adam8 was recently correlated with lung cancer (Ishikawa et al, 2004). Coregulation of genes exposed by the SOM algorithm provides a basis for the identification of new concepts of transcriptional regulation and important transcription factors necessary for tumour promotion and progression into malignant tumour stages.…”
Section: Discussionmentioning
confidence: 82%
“…To test this hypothesis, we examined the effect of ERK inhibition on the induction of the p19 ARF promoter. Fra-1-containing dimers were shown to be phosphorylated by the ERK kinase pathway (Young et al, 2002). The inhibition of ERK using the U0126 drug significantly reduced induction of the p19 ARF promoter by the c-JunBFra-1 dimer, suggesting that ERK activity is essential for AP-1 regulation of the ARF gene (Figure 5e).…”
Section: Ap-1 Dimers Regulate the Mouse P19 Arf Genementioning
confidence: 99%